Perhitugan TKDN Pada Produk (Barang) Guna Meningkatkan Perekonomian Dalam Negeri - Alfiatus Zainiyah; Ni Made Ida Pratiwi (Politeknik Kampar, 2024)
In improving domestic industrial businesses, the government must be able to increase the Use of Domestic Products (P3DN). The TKDN policy also reduces dependence on foreign products, creating jobs. The calculation of the Domestic Component Level is an important evaluation method in industry to measure how much of the components in a product are produced domestically. This research uses the literature review method. The purpose of this research is to find out “Calculation of TKDN products to improve the domestic economy”.